2012
DOI: 10.1080/09500693.2012.749362
|View full text |Cite
|
Sign up to set email alerts
|

To Choose or Not to Choose Science: Constructions of desirable identities among young people considering a STEM higher education programme

Abstract: In the literature, there is a general concern that a less number of students choose to study science, technology, engineering or mathematics (STEM). This paper presents results from a Danish longitudinal study which examines students' choice of whether or not to continue studying STEM after upper-secondary school. In particular, this study focuses on students who held an STEM subject as one of their favourite subjects at secondary educational level, but who chose not to study STEM at the tertiary level. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(69 citation statements)
references
References 19 publications
2
58
0
3
Order By: Relevance
“…Research with middle school students has confirmed the importance of this variable in predicting career intentions (Fouad & Smith, 1996). Qualitative studies, relying on in-depth interviews, have also shown the importance of career prospects (along with basic interest in science) in student decisions to pursue STEM higher education (Holmegaard, Madsen, & Ulriksen, 2014).…”
Section: Outcome Expectancymentioning
confidence: 95%
“…Research with middle school students has confirmed the importance of this variable in predicting career intentions (Fouad & Smith, 1996). Qualitative studies, relying on in-depth interviews, have also shown the importance of career prospects (along with basic interest in science) in student decisions to pursue STEM higher education (Holmegaard, Madsen, & Ulriksen, 2014).…”
Section: Outcome Expectancymentioning
confidence: 95%
“…Students who choose not to take science studies, imagine science careers as having no opportunities for future self-development and positions of influence (Holmegaard, Madsen, & Ulriksen, 2014). Negative conceptions dominate.…”
Section: Introductionmentioning
confidence: 99%
“…Here the aim was both to move across the data set and also to look deeper into some specific narratives. The quotes from students' narratives presented in this paper were selected as illustrations of the various patterns found in the analysis of the sub-themes (for an extensive presentation of the analytic approach see Holmegaard et al, 2014b).…”
Section: Analytic Approachmentioning
confidence: 99%
“…We documented how the choice of HE paths is a continuous and dynamic process, in which students' choices can change dramatically within a short time. Rather than being one single decision, we showed how students continuously negotiate and re-construct their choices (Holmegaard, Madsen, & Ulriksen, 2014a, 2014bHolmegaard, Ulriksen, & Madsen, 2014;Holmegaard, Ulriksen, & Madsen, 2015). The aim of this paper was to unpack this process and the steps students take on their way, and hence analyse the patterns that appear in this process of choosing what to continue studying after upper secondary school.…”
Section: Introductionmentioning
confidence: 95%